Web Accessibility Analysis of Indonesia Inclusive Vocational High Schools - Ranu Iskandar; Rizki Setiadi; Angga Septiyanto; Ampapan Tuntinakhongul (My University, 2022)
Students with disabilities have the same rights as normal students in accessing the inclusive vocational high school webs. This study aims to analyze the web accessibility of inclusive vocational high schools for students with disabilities. This research is a qualitative descriptive research. Website accessibility was analyzed using Taw, Wave, and Achecker. There are 42 inclusive vocational high school websites that will be the source of data. The results of the analysis of the 3 tools were then compared and described. Web accessibility of Indonesia inclusive vocational high schools using TAW, the most problems that arise are operable aspects, when using ACheker the most problems that arise are non-text content, and when using wave the most common problem is error contrast.
Keywords: Digital Accessibility for Disabilities; Mobile and Web Applications; Assistive Technology in Communication and Mobility